Knowledge Level of Students via Capacity Building Programme on Scientific Lac Cultivation, Processing, Uses and their Correlates (Indian Journal of Extension Education, 2017)
The impact of capacity building programme on scientific lac cultivation, processing and uses in terms of knowledge level of students was carried out during January to June 2014 at ICAR-Indian Institute of Natural Resins & Gums (IINRG) Namkum, Ranchi. During the period, IINRG conducted 03 courses exclusively for students of undergraduate & postgraduate students, in which 151 participants participated. Out of 151 participants, 110 students were randomly selected as respondents for this study. The investigation showed education, occupation, farm size, monthly income, social participation and sources of information were positively and significantly related to knowledge level of students at 5 percent level of probability and their t values were 3.14, 2.45, 4.32, 3.64, 4.44 and 3.47, respectively. Maximum respondents have very optimistic views towards scientific lac cultivation and few respondents have below average knowledge level towards scientific lac cultivation. It also revealed that the impact of capacity building programme was knowledge gain after training was significantly high among students for all the lac cultivation practices.